Automation and scale-up of human induced pluripotent stem cell models of cardiovascular disease for drug screening - Crutchley, James E.B. (James Crutchley, 2016)
The global cost of heart failure is USD$45 billion and set to double in the next 15 years. The only method of treatment is heart transplant but demand far exceeds supply and is projected to increase. Meanwhile, global pharmaceutical development has been hindered by poor drug development success rates. Of the drugs that make it to phase I clinical trials, only 8 % pass phase III and existing drug screens do not always accurately predict or detect adverse cardiac events. Cardiotoxicity is the underlying reason for 26 % of safety related drug withdrawals between 1990-2006. Therefore, a source of human cardiomyocytes (CMs) is required to fill the need for regenerative medicine and drug screening applications. Differentiation of human pluripotent stem cells (hPSCs) to CMs is a viable solution to this bottleneck but the number of cells required is staggering; up to 5 million novel compounds are registered annually by pharmaceutical and academic institutions, while cell replacement studies in primates suggest that 10 billion CMs will be required per patient to repair the damaged myocardium post infarction.